Arabic Language Program Management for Muhadatsah Class - Rifki Zaitul Ikhlas; Krim Ulwi; Patri Patri (Journal of Arabic Literature, Teaching and Learning, 2025)
Faced with a growing demand for Arabic language learning, course institutions such as OCEAN Pare Arabic language course institution are faced with the responsibility of providing quality education. Effective program management is key in ensuring optimal learning quality. This study aims to find out the organizing management practices in the Arabic language program of muhadatsah class at Ocean Pare Arabic language course institution. This study used a qualitative approach using interview techniques and document analysis. Data were collected from various sources, teachers, institute managers, as well as related documents. Data analysis was conducted to understand how the program was organized and managed. The result of this study is that OCEAN Pare Arabic language course institution implements a management system that includes planning, organizing, implementing, and supervising. In planning, the institution sets a vision of creating a smart generation through Arabic language education with a mission to improve teaching effectiveness and love for knowledge. Organizing is done with a clear organizational structure, teacher qualifications determined by the mudir, and recruitment of students every month. Program implementation consists of classroom and dormitory learning activities with various levels of Arabic language proficiency and daily practice. Supervision is carried out through daily, weekly and end-of-program evaluations, as well as control in the dormitory by musyrifs.